ANALYSIS OF MANGROVE BIOMASS IN THE ECO – TOURISM AREA OF MANGROVE ECOSYSTEM IN SUNGAITOHOR VILLAGE OF RIAU PROVINCE - Antonius '; Dessy Yoswaty; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in December 2016-January 2017 in the mangrove ecosystem of Sungaitohor Village, Riau Province. The objective of this research was to analyze the biomass potential of mangrove ecosystem, to know the difference betwen above ground biomass potential (Above Ground Biomass, AGB) and underground biomass (Below Ground Biomass, BGB). Of the ANOVA test results on the levene test count has a value of 5.822 with a probability value of 0.009 (<0.05) then the three variants of the population are identical so that the biomass content of Station 1. Station 2 and Station 3 is not significantly different, the results showed that in the t-independent test results showed no significant differences in the potential value of AGB and BGB. Based on the ANOVA test the finding shawed no significant difference to total biomass at each station in Sungaitohor Village, Meranti Islands District.Keyword : Mangrove, Biomass, Sungaitohor, Meranti